The prevalence and factors affecting primary dymenorrhea among female students - Nur Syafiqa Azli,; Atirah Mohd Zawawi,; Nur Syafiqah Ibrahim,; Shamsunarnie Mohamed Zukri,; Noor Zafarina Mohd Fauzi,; Fukayhah@Fatiha Suhami, (Penerbit Universiti Kebangsaan Malaysia, 2021)
Hospitals are health care institution that provides medical and surgical treatment and nursing care for sick or injured people. Primary dysmenorrhea is acramp-like pain that usually felt in the lower abdomen. The study was conducted to determine ‘The Prevalence and Factors Affecting Primary Dysmenorrhea among Female University Students. A cross-sectional design was used in this study. The sample size of 268 female students from Universiti Teknologi MARA Cawangan Kelantan, Kampus Kota Bharu (UiTMKB) was obtained by using Proportionate Stratified Random Sampling technique. A validated self-administrated structured questionnaire was used for data collection. Descriptive Statistics, Chi-square test and Binary Logistic Regression analysis was performed for this study. The prevalence of primary dysmenorrhea among UiTMKB female students was 60.4%. There was a significant association between primary dysmenorrhea status with menstrual blood loss, family history, stress level and carbonated drink intake. Moreover, there were a significant impact caused by primary dysmenorrhea on students’ daily activities. The finding also indicated the factors that affecting the primary dysmenorrhea were only menstrual flow, menstrual blood loss and family history. Therefore, for those who experienced normal average duration of menstrual blood flow, heavy/ heavy with clots of menstrual blood loss and their family members experienced period pain were advised to refer to the doctor for further treatment.